Nursi’s Sufism Without Sufi Order: A Centemporary Debate Among The Ulama - Siswoyo Aris Munandar; Jazilus Sakhok; Puji Astuti; Elia Malikhaturrahma (Jurnal Ushuluddin, 2020)
Some scholars think that people who take up religious beliefs are synonymous with being committed so that many people want to have tarekat. Even so, there are scholars like Badiuzzaman Said Nursi who think that tasawuf does not have to be committed. The statement of Sufism and sufi order according to Nursi is a way to recognize the nature of faith and the essence of the Qor’an to become a spiritual path under the guidance of the Prophet's sunnah. For Nursi, the spiritual activator is dhikr to Allah and continuous tafakkur to eliminate gloom, fear, and a sense of alienation from humans. The problem in this research is how the basic thoughts of Sufism Nursi and how the thoughts of Nursi about tasawuf without being committed. This study aims to determine the thoughts of Nursi about Sufism without any commitment. The results of this study are expected to provide a new understanding of the context of Sufism. This research is qualitative research that emphasizes library research. The type of approach carried out uses a socio-historical approach. Data collection was done by using the documentation method. Data analysis was performed using content analysis techniques. The analysis was carried out by proving the contents of the book, then analyzed and matched with existing data. This research also uses the method of interpretation (hermeneutic) so that Nursi's thoughts can be understood in a broader context and his childhood Nursi and his family adhered to the Nahsyabandiyah sufi order. Even so, Nursi stated firmly that he was not a follower of a sufi order. If the conventional view says that the nature path must be through sufi order, Nursi says: the nature path is sufficient through the Qur'an and following the behavior of the Prophet Muhammad. These characteristics can be used to describe al-Nursi's model of Sufism, namely sufism without sufi order. The results showed that Sufism without sufi order, according to Nursi, is someone who has sufism does not have to follow the teachings of a sufi order that has a teacher or murshid, only by always making dhikr glorifying the name of Allah, and always carrying out God's mandatory commands and sunnah so he will feel close God. I think Nursi thinking is something new that will make it easier for someone to be closer to Allah